Self-regulation and the intention behaviour gap: Exploring dietary behaviours in university students - Mullan, Barbara; Allom, Vanessa; Brogan, A.; Kothe, E.; Todd, J. (Elsevier BV, 2014)
The aim of this study was to explore whether two aspects of self-regulation (impulsivity and temporal orientation) could reduce the intention–behaviour gap for two dietary behaviours: fruit and vegetable consumption and saturated fat consumption. Australian undergraduate students (N = 154) completed questionnaires (the Barratt impulsiveness scale and the consideration of future consequences scale) and intention measures, and 1 week later behaviour was measured using the Block rapid food screener. After controlling for demographics, intention was associated with fruit and vegetable consumption, but the self-regulation measures did not further improve the variance accounted for. For saturated fat, gender was associated with consumption, such that males tended to consume more saturated fat. Intention was significantly associated with consumption, and impulsivity further improved the model such that those who were more impulsive tended to consume more saturated fat. These findings suggest that health protective and health risk behaviours, such as those investigated in the current study, may have different determinants.